Analysis Method Teaching Teacher Physical Education Based Game Traditional Enjang - Enjang - Rusdiana Yusuf; I Wayan Lasmawan; I Gusti Putu Suharta; I Wayan Widiana (Yayasan Baru Haji Samsudin, 2025)
This study aims to analyze the teaching method of physical education, sports, and health (PJOK) based on the traditional game of enjang-enjang. The background of this study departs from the need for a contextual, fun, and local wisdom-based learning approach in accordance with the demands of the Independent Curriculum. Traditional games are seen as having educational and character values that can enrich students' learning experiences. This study used a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with teachers and students, and documentation. The results showed that the enjang-enjang-based teaching method was able to increase learning motivation, active involvement, and the formation of student character such as sportsmanship, responsibility, and cooperation. Teachers designed and implemented learning systematically by integrating local cultural values into the lesson plan (RPP). Supporting factors for the success of this method included school support, student enthusiasm, and teacher readiness. Meanwhile, obstacles faced included limited learning time, unpredictable weather, and students' unfamiliarity with the game rules. However, teachers were able to overcome these obstacles through adaptive strategies. These findings indicate that the integration of traditional games into physical education (PJOK) learning is not only curricularly relevant but also effective in shaping students' character, contextualization, and appreciation for local culture